Heterogeneity in making: Findings, approaches, and reflections on inclusivity in making and makerspaces - Fuchsberger, Verena; Smit, Dorothé; Campreguer França, Nathalia; Gerdenitsch, Cornelia; Jaques, Olivia; Kowolik, Joanna; Regal, Georg; Roodbergen, Emma (Frontiers in Human Dynamics, 2023)
Making, i.e., the hobbyist and technologically-based creation of things, has been associated with many benefits. It is considered to contribute to the development of skills and to enable participation in innovation, and even democracy. At the same time, institutionalized making (in makerspaces, fablabs) is known to be exclusive as members of such spaces are very often young, well-educated, white men. This is in contradiction to the promise and self-understanding of the maker culture, which aims to be open and inclusive. In the past three years, we, a group of researchers, makers, fablab employees, hackerspace operators, and artists, have engaged with such disparities in a collaborative research project. We inquired into barriers that women* and other underrepresented groups experience, created visions to change the status quo, and implemented smaller and bigger interventions in different spaces (fablab, hackerspace, makers’ homes) to explore their impacts. In this article, we discuss findings, approaches, and foremost, reflections and experiences. Besides presenting selected insights from our explorations, we pay particular attention to the tensions and challenges that we encountered during our research endeavors. Many of those are rooted in our own roles, perspectives, and backgrounds - which are multiple, sometimes conflicting, troubling, frustrating, yet enriching, and rewarding. In the form of a written conversation among project members, we present those different viewpoints, connect them where possible and oppose them where needed. We conclude by articulating tensions that we see as characteristic regarding making and the research around it.